How Does AI Enable Remote Rehabilitation Services? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2015)
The global demand for rehabilitation services is rapidly increasing, driven by an aging population and a rise in chronic health conditions [1]. Traditional r...
Keywords: Telemedicine and Digital Health; Enable; Remote; Rehabilitation; Artificial Intelligence; Machine Learning; Healthcare